High-intensity interval training every second week maintains VO2max in soccer players during off-season - Slettaløkken, G.; Rønnestad, B. R. (The Journal of Strength and Conditioning Research, 2014)
Reduced endurance training among semiprofessional soccer players during off-season may have negative effect on game performance during the competition season. This negative effect can be prevented by adding high-intensity interval training (HIT) to normal activity. In this study, we want to compare 2 different frequencies of HIT (5 bouts of 4 minutes on 87-97% peak heart rate) session on maintenance of aerobic fitness among semiprofessional soccer players during a 6-week off-season period. Seventeen male players at second and third highest soccer division in Norway participated. The subjects were randomized into 1 HIT session every second week (HIT 0.5) or 1 HIT session per week (HIT 1). All participants performed a 20-m shuttle run test and a maximal oxygen uptake (VO2max) test on treadmill before and after the training intervention. VO2max (HIT 0.5, 63.4 ± 5.9 ml/kg/min; HIT 1, 65.6 ± 2.1 ml/kg/min) and 20-m shuttle run performance (HIT 0.5, 2335 ± 390 m, HIT 1, 2531 ± 106 m) were not different between the groups before the training intervention. VO2max was maintained after the training intervention in both HIT 0.5 and HIT 1 (64.0 ± 5.9 ml/kg/min and 64.3 ± 1.3 ml/kg/min, respectively). There was a reduction in distance covered during the 20-m shuttle run test in HIT 1 and when groups were pooled (-7.9 ± 5.7% and -6.4 ± 7.9%, respectively, p < 0.05). In conclusion, HIT 1 did not maintain VO2max better than HIT 0.5 when added to normal off-season activity. However, performance in 20-m shuttle run, which is a more soccer-specific fitness test than VO2max test, was slightly reduced when both groups was pooled.